Vasoconstrictor response to cold in forestry workers: a prospective study. Issue 1 (January 1988) - Olsen, N; Nielsen, S L
Abstract : In a five year prospective study of the vasoconstrictor response to cold 37 forestry workers were investigated in 1978 and again in 1983. The subjects were classified into three groups: group A (n = 13): no subjective finger symptoms in 1978 and continued sawing until 1983; group B (n = 12): no symptoms in 1978 and stopped sawing before 1983; group C (n = 12): vibration induced white finger (VWF) in 1978. A cold provocation test measuring the finger systolic blood pressure with a cuff and strain gauge technique during combined body cooling and finger cooling to 30 degrees, 15 degrees, and 6 degrees C was applied to all subjects at both investigations. In 1978 all groups had an increased cold response when compared with that of 20 non-exposed controls (p less than 0.05), and the response was more exaggerated in group C than in groups A and B (p less than 0.01). From 1978 to 1983 the vasoconstrictor response increased in group A (p less than 0.05), was in group B (p greater than 0.10), and improved in group C (p less than 0.05). The changes in cold response in groups A and C were significantly larger than the within day variation of the method (p less than 0.01). The aggravation of group A indicates that a further five years use of anti-vibration chain saws induced an increased hyperreactivity in the vasoconstrictor mechanisms but led to subjective symptoms of VWF in only one subject. The improvement in group C was in accordance with the improvements of subjective finger symptoms and was associated with a previous shift from saws without vibration damping devices to anti-vibration saws and with cessation of work. The results of group C indicate that VWF may improve or subjectively disappear if exposure to vibration is reduced or stopped. The cold provocation test was more sensitive than the Taylor-Pelmear stage assessments (p<0.05). The test may be of guidance in evaluation preventive measures.